In Vitro Folliculogenesis in Mammalian Models: A Computational Biology Study - Bernabò, Nicola; Di Berardino, Chiara; Capacchietti, Giulia; Peserico, Alessia; Buoncuore, Giorgia; Tosi, Umberto; Crociati, Martina; Monaci, Maurizio; Barboni, Barbara (Frontiers in Molecular Biosciences, 2021)
In vitro folliculogenesis (ivF) has been proposed as emerging technology to support follicle growth and oocyte development. It holds many attractions from preserving human fertility to improving animal reproductive biotechnology. Despite the mice model, where live offspring have been achieved, in medium-sized mammals ivF has not validated yet. Thus, the employment of a network theory approach has been proposed for interpreting the large amount of ivF information collected to date in different mammalian models in order to identify the controllers of in vitro system. The WoS-derived data generated a scale-free network, easy navigable including 641 nodes and 2089 links. A limited number of controllers (7,2%) are responsible for network robustness by preserving it against random damage. The network nodes were stratified in a coherent biological manner on 3 layers: the input that was composed of systemic hormones and somatic-oocyte paracrine factors, the intermediate one recognized mainly key signaling molecules such as PI3K, KL, JAK-STAT, SMAD4 and cAMP and the output layer molecules were related to functional ivF endpoints such as FSH receptor and steroidogenesis. Notably, the phenotypes of knock-out mice previously developed for hub.BN indirectly corroborate their biological relevance in early folliculogenesis. Finally, taking advantage of STRING analysis approach, further controllers belonging to metabolic axis backbone were identified such as mTOR/FOXO, FOXO3/SIRT1 and VEGF that have been poorly considered in ivF to date. Overall, this in silico study identifies new metabolic sensor molecules controlling ivF serving as a basis for designing innovative diagnostic and treatment methods to preserve female fertility.